ANALISIS PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IIIa DI UPTD SD ISLAM NEGERI COKROAMINOTO 2 KALABAHI - Leni Adriana Jalla; Triznawasti Y. Daik; Nehemia Fanpada (STKIP Subang, 2026)
Jalla Adriana Leni. 22586026063. Analysis of the Implementation of Differentiated Learning in Pancasila Education Subject for Class IIIa at UPTD SD Islam Negeri Cokroaminoto 2 Kalabahi.Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Tribuana Kalabahi University. Supervisor I: Triznawasti Y. Daik, S.Pd., M.Pd., and Supervisor II: Nehemia Fanpada, S.Pd., M.Pd. Pancasila Education learning in elementary schools needs to be supported by differentiated learning to accommodate the diversity of students' characteristics. Differentiation is an approach that adjusts content, process, and product of learning based on students' needs. This study aims to determine the implementation of differentiated learning in the Pancasila Education subject in class IIIa at UPTD SD Islam Negeri Cokroaminoto 2 Kalabahi. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. Research subjects consisted of the teacher and students of class IIIa. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicated that differentiated learning has been implemented through content, process, and product differentiation. The teacher mapped students' learning needs based on readiness, interests, and learning styles. Role-playing methods and various instructional media were applied to accommodate student diversity. However, implementation still faced challenges, including time constraints and limited learning resources. Overall, differentiated learning in Pancasila Education in class IIIa has proceeded well, though improvements in planning and implementation remain necessary to optimize learning outcomes according to students' needs.